Educational accountability of faculty and students in Higher Education: A prospective policy analysis - Khalil, Marwa (AUC Knowledge Fountain, 2017)
The purpose of this research is to examine the current quality assurance and accountability policies and practices in Egyptian public higher education institutions. It specifically examines the perceived effectiveness of pedagogical and assessment practices on students’ learning and institutional performance. The paper seeks to analyze the current challenges to propose a new policy to promote accountability of faculty and students. This qualitative research paper follows what Patton (2002) termed “prospective policy analysis”. Participants were selected using the purposive sampling technique. Fifty-one participants comprised the sample of the study. They were chosen from two accredited programs in two public universities in Greater Cairo. A Humanities program was chosen from University X; and an Engineering program was chosen from University Y. Two department heads, twenty faculty members and twenty-nine undergraduate fourth year students were involved in the study. Data was collected over the period of two weeks through semi-structured interviews, focus groups and document analysis. Data was analyzed using the thematic approach. Findings revealed many faculty members and students confirm that the current policies and practices are not effective. They have identified that large students numbers as one of the major challenges. Based on Delphi technique, the recommended prospective policies are “accountability policy for professors”, “new admission policy” and “reforming assessment practices”.